The Application of Sufi Values to Overcome Academic Stress Among University Students - Muhamad Danish; Arif Wibowo (STAI Yogyakarta, 2026)
Academic stress remains a pervasive challenge among university students, primarily driven by intense study demands, accumulating assignments, and stringent time constraints. If left unmanaged, this condition can escalate into academic burnout, severely compromising students' psychological well-being and overall mental health. While contemporary psychology provides various intervention strategies, these approaches are frequently confined to empirical and secular frameworks, often neglecting the underlying spiritual crises experienced by individuals. This study comprehensively investigates the application of Sufi (tasawuf) values as a holistic spiritual coping mechanism to mitigate academic stress among college students. Utilizing a library research method with a descriptive qualitative approach, this study analyzes relevant literature across Sufism, Islamic counseling, and modern psychology. The primary research gap addressed is the limited integration of Sufi spiritual frameworks with contemporary psychological coping theories within the context of Indonesian students. The novelty of this research lies in the proposition of a synthesized model that intricately connects the internalization of core Sufi values—specifically tawakkul, dhikr, muhasabah, and sabar— with scientifically recognized psychological coping mechanisms. The findings indicate that these Sufi practices serve as highly efficacious spiritual coping strategies: tawakkul acts as arobust psychological buffer against academic pressure; dhikr functions as an instrument for neurological and emotional relaxation; and muhasabah facilitates structured self-reflection analogous to cognitive restructuring. In conclusion, Sufism transcends mere theologicalabstraction, serving as a profound, holistic psychological tool that tangibly contributes to sustaining students' mental equilibrium and academic motivation.